Low pressure ammonia oxidation over supported cobalt catalyst for nitric acid production - Fung, Wing-Kin (Department of Chemical Engineering, 2016)
Ammonia oxidation is used in the production of nitric acid. The process is either run at high pressure or low pressure, with the latter requiring larger equipment. Platinum gauze is typically used as a catalyst operating at high temperatures (in the range of 810-940 ᵒC). The platinum based catalyst is highly active and highly selective in producing the desired NOₓ products, with some formation of the undesired byproducts, i.e. N₂, N₂O and N₂O₄. However, a significant amount of platinum is lost during the process due to platinum volatilisation resulting in plant operating times varying between 2-12 months. Furthermore, the loss of platinum is the 2nd largest expense of the operation. Platinum loss can only be minimised but not eliminated, thus a variety of metal oxide catalysts for oxidation of ammonia to nitrogen oxides have been studied. Cobalt oxide seems to be the most promising alternative for platinum exhibiting a high activity and selectivity towards NO. The aim of this study is to explore the use of a supported cobalt Co₃O₄ on silica catalyst for ammonia oxidation and compare some of the results with a commercial catalyst consisting of a pure, unsupported Co₃O₄.